2012
DOI: 10.1371/journal.pone.0037883
|View full text |Cite
|
Sign up to set email alerts
|

Betaine and Secondary Events in an Acute Coronary Syndrome Cohort

Abstract: BackgroundBetaine insufficiency is associated with unfavourable vascular risk profiles in metabolic syndrome patients. We investigated associations between betaine insufficiency and secondary events in acute coronary syndrome patients.MethodsPlasma (531) and urine (415) samples were collected four months after discharge following an acute coronary event. Death (34), secondary acute myocardial infarction (MI) (70) and hospital admission for heart failure (45) events were recorded over a median follow-up of 832 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 52 publications
5
63
0
1
Order By: Relevance
“…Svingen et al 7 also reported a high coefficient of reliability (0.93) for plasma DMG in people with stable angina. Plasma DMG was also shown to be predictive of secondary cardiovascular events, 7 which is in agreement with the findings of Lever et al 6 The predictive value of single Median values were calculated from all four time points. The coefficients of reliability for the urine results were calculated on log-transformed data because the data were not normally distributed.…”
Section: Individualitysupporting
confidence: 87%
See 1 more Smart Citation
“…Svingen et al 7 also reported a high coefficient of reliability (0.93) for plasma DMG in people with stable angina. Plasma DMG was also shown to be predictive of secondary cardiovascular events, 7 which is in agreement with the findings of Lever et al 6 The predictive value of single Median values were calculated from all four time points. The coefficients of reliability for the urine results were calculated on log-transformed data because the data were not normally distributed.…”
Section: Individualitysupporting
confidence: 87%
“…3 Urinary betaine excretion is often elevated in diabetes and renal failure. 4,5 Plasma betaine concentrations and urinary betaine excretions can predict secondary cardiovascular events in people with established vascular disease, 6 and the plasma concentration of dimethylglycine, the product of betaine metabolism, is an especially strong prognostic marker. 6,7 These predictions are stronger for patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A cross‐sectional analysis in HUSK suggested that high choline and low betaine plasma concentrations were associated with an unfavorable cardiovascular risk profile 31. A study among patients with established coronary heart disease reported that both high and low plasma betaine concentrations were associated with an increased risk of later coronary events and hospitalization for heart failure 32. In WENBIT patients with stable angina pectoris, elevated plasma choline levels were associated with an increased risk of acute myocardial infarction in nonsmoking patients 6…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NAME population consisted of community-dwelling elders in contrast with patient populations who have been studied by other authors. For example, a study of a cohort with acute coronary syndrome concluded that high and low plasma betaine concentrations were associated with increased risks of secondary heart failure and acute myocardial infarction, respectively (24). A second study in the same cohort concluded that lower plasma betaine concentrations were associated with higher concentrations of triglycerides and non-HDL cholesterol (25).…”
Section: Discussionmentioning
confidence: 99%